The discovery of two spotted leopards (Panthera pardus) in Peninsular Malaysia - Tan Kai Wei, Cedric; Moore, Jonathan; Saaban, Salman; Campos-Arceiz, Ahimsa; Macdonald, David W. (Mongabay.com, 2015)
We discovered the presence of two individual spotted leopards Panthera pardus in Ulu Muda Forest Reserve, a previously under-researched selectively logged rainforest of Peninsular Malaysia. These findings are unexpected, because only two other studies have detected the spotted morph amongst many other melanistic leopards caught on camera traps in Peninsular Malaysia. We discuss the implications of our findings with respect to the prevalence of melanism among leopards in the region.